1998
DOI: 10.1006/viro.1998.9373
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Clade-Specific Cytotoxic T Lymphocytes in HIV-1-Infected Children

Abstract: We studied cytotoxic T lymphocyte (CTL) cross-reactivity between human immunodeficiency virus type 1 (HIV-1) subtypes within a group of infants infected with either HIV-1 B or non-B clade. Fifteen children were infected with a clade B virus. Nine were infected with non-B virus, including two clade A, four clade D, two clade F, and one clade G. CTL activities from in vitro activated peripheral blood mononuclear cells were tested against autologous cell line infected with recombinant vaccinia viruses encoding fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…Early studies of the HIV-1-specific CTL response among perinatally infected children indicated that these responses emerge later and are generally weaker and narrower than in their adult counterparts (9,11,25,26,30,38,40). However, these studies relied on techniques that are less sensitive than those currently available and that provide no information about the epitopes targeted or the overall breadth of response.…”
mentioning
confidence: 99%
“…Early studies of the HIV-1-specific CTL response among perinatally infected children indicated that these responses emerge later and are generally weaker and narrower than in their adult counterparts (9,11,25,26,30,38,40). However, these studies relied on techniques that are less sensitive than those currently available and that provide no information about the epitopes targeted or the overall breadth of response.…”
mentioning
confidence: 99%
“…Seven children included in a longitudinal follow-up study of their CTL activities were selected for their expression of HLA-B53 or -B57, as determined by amplification refractory mutation system PCR (4,5). Peripheral blood mononuclear cell (PBMC) samples exhibiting significant lysis against the HIV p55 gag protein were chosen for this study.…”
mentioning
confidence: 99%
“…Mother-to-child transmission of HIV was responsible for infection of the other children. Their infecting subtypes were determined by heteroduplex mobility assay or sequencing of the Env gene, as previously reported (5). Patients' clinical and biological characteristics are summarized in Table 1.…”
mentioning
confidence: 99%
“…The extent of CD8 + T cell cross-reactivity remains controversial with evidence both for [10][11][12][13][14][15][16][17] and against [18][19][20][21][22] its broad effectiveness. At least in the one animal tested on two occasions, we observed cross-reactivity of CD8 + T cells with 50% of tested epitope variants not present in the vaccine (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have addressed this point with mixed results. While some studies clearly detected cross-clade-reactive HIV-1-specific CD8 + T cell responses [10][11][12][13][14][15][16][17], there is substantial evidence that CD8 + T cells can be highly sequence-specific [18][19][20][21][22]. This was best demonstrated in systematic studies employing all possible single amino acid substitutions in each position of an MHC class I epitope, which suggested that as few as one in three epitope variants was recognized by a given T cell receptor [18,23].…”
Section: Introductionmentioning
confidence: 99%